การศึกษาการใช้การบำบัดทางความคิดและพฤติกรรมต่อความวิตกกังวลในผู้ป่วยโรควิตกกังวล สถานีอนามัยบ้านดอนกลาง จังหวัดสุพรรณบุรี - เนตรทราย หอละเอียด (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objective of this independent project study was to compare the anxiety of patients with anxiety disorder at Bandonklang Healthcenter, Suphanburi Province before and after receiving the cognitive behavior therapy. The study sample were 20 patients with anxiety disorder who met the inclusion criteria. The instruments for this study were the cognitive behavior therapy plan, and State-Trait Anxiety inventory (STAI formYl). The instruments were examined for content validity by three professional experts. The Cronbach’s Alpha Coefficient reliability of the State-Trait Anxiety inventory was 0.90. Statistical techniques used for data analysis were percentage, mean, standard deviation and paired t-test. The major finding was as follow: State -Trait Anxiety of patients with Anxiety disorder who received the cognitive behavior therapy was significantly lower than before received the cognitive behavior therapy at the .05 level.